KELOLA SAMPAH MENJADI PUPUK ORGANIK BERBASIS MASYARKAT DI RW. 06 KELURAHAN KRUKUT KOTA DEPOK - Sri Sulasminingsih; Budhi Martana; Subur Subur (LPPM UPN Veteran Jakarta, 2018)
Abstract Household waste in the form of organic and non-organic materials can be used as economically valuable materials. The Community Service Program was held for 2 months at the RW. 06 Krukut Urban Village, Depok City. The program aims to (1) increase public awareness of the importance of managing and processing waste independently, (2) increasing community knowledge and insight that waste processing units do not cause air pollution, sources of disease, and inconvenience, (3) increase community knowledge and insight into variousindependent composting techniques, and (4) provide training to the community about processing waste into organic fertilizers that have economic value. The method used is to provide training on waste management and its application in daily life. Organic material can be used as organic fertilizer using a composter, processing waste that is practiced in a clean, clean and odorless manner so it is very safe to use for household scale. The output target of the Community Service program is (1) the community begins to realize the importance of managing andprocessing waste independently, (2) the community has the knowledge and ability about the techniques of processing waste into organic fertilizer, and (3) the active participation of the community in solve the problem of garbage sorting systems starting from households, so that a clean, comfortable and free environment from waste pollution is created.